English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

what are the steps

2007-01-18 17:09:29 · 2 answers · asked by Anonymous in Science & Mathematics Mathematics

2 answers

for what????
(-8 radical x + radical y) ( radical x+8 radical y)
= ( -8 sqrt(x) + sqrt(y) ) (sqrt(x) +8sqrt(y) )
=-8 x -64sqrt(x)sqrt(y) +sqrt(x)sqrt(y) + 8 y
= -8 x -63sqrt(x)sqrt(y) + 8 y .

2007-01-19 06:36:03 · answer #1 · answered by tablecloth 1 · 0 0

I assume you want to multiply it out. Use the FOIL method.
Multiply the:

First terms
Outside terms
Inside terms
Last terms

(-8√x + √y)(√x + 8√y)
= (-8√x)(√x) + (-8√x)(8√y) + (√y)(√x) + (√y)(8√y)
= -8x - 64√(xy) + √(xy) + 8y
= -8x - 63√(xy) + 8y

2007-01-18 17:26:35 · answer #2 · answered by Northstar 7 · 0 0

fedest.com, questions and answers